Utilisation of evidence-based practices by ASD early intervention service providers. (February 2017) - Paynter, Jessica M; Ferguson, Sarah; Fordyce, Kathryn; Joosten, Annette; Paku, Sofia; Stephens, Miranda; Trembath, David; Keen, Deb
A number of autism intervention practices have been demonstrated to be effective. However, the use of unsupported practices persists in community early intervention settings. Recent research has suggested that personal, professional and workplace factors may influence intervention choices. The aim of this research was to investigate knowledge and use of strategies, organisational culture, individual attitudes, sources of information and considerations informing intervention choices by early intervention providers. An online survey was completed by 72 early intervention providers from four organisations across Australia. Providers reported high levels of trust and access of information from internal professional development, therapists and external professional development. A range of considerations including child factors, family values and research were rated as important in informing intervention choices. Participants reported greater knowledge and use of evidence-based and emerging practices than unsupported. Levels of use were linked to levels of knowledge, as well as some organisational and attitudinal factors. Areas for future research and implications are discussed.